Military power and politics in black Africa Vol. 1 - Baynham, Simon 1950- (London: Routledge, 1986)
First published in 1986, Military Power and Politics in Black Africa explores many themes that concerned military power and politics in sub-Saharan Africa at the time of publication. Adopting a thematic approach, the book considers the nature of both intervention and disengagement and looks at the relationship between civilian and military institutions. The final chapters put forward arguments for the importance of foreign intervention in the politics and civil-military relations of African states.
1: Introduction: Armed Forces in Africa, Simon Baynham; 2: Military Rule in Africa: Etiology and Morphology, Samuel Decalo; 3: Military Disengagement from Politics? Incentives and Obstacles in Political Change, Claude E. Welch, Jr. 4: Armies and Politics in Civilian Regimes, David Goldsworthy; 5: Revolutionary Armies of Africa: Mozambique and Zimbabwe, Annette Seegers; 6: Pax Africana? Dennis Austin; 7: Armies on Loan: Toward an Explanation of Transnational Intervention Among Black African States: 1960-85, Arnold Hughes and Roy May; 8: Foreign Intervention in Africa, Anthony Clayton; 9: Arms Control in Africa, Abbott A. Brayton; 10: South Africa's Military Relations with its Neighbours, J. E. Spence; Index
Includes bibliographical references and index.
Simon Baynham
Keywords: Since 1960; Civil-military relations -- Africa, Sub-Saharan.; Relations pouvoir civil-pouvoir militaire -- Afrique subsaharienne; HISTORY -- Military -- General; POLITICAL SCIENCE -- General; POLITICAL SCIENCE -- Political Freedom & Security -- General; Armed Forces; Armed Forces -- Political activity; Civil-military relations; Politics and government; Africa, Sub-Saharan -- Armed Forces; Africa, Sub-Saharan -- Armed Forces -- Political activity; Africa, Sub-Saharan -- Politics and government -- 1960-; Afrique subsaharienne; Afrique subsaharienne -- x; Afrique subsaharienne -- Politique et gouvernement -- 1960-; Sub-Saharan Africa